Changes in dairy cows’ temperature - isaksson, jessica (SLU/Dept. of Anatomy, Physiology and Biochemistry (until 231231), 2017)
Lactating cows have a higher heat production due to the milk synthesis compared to dry cows. In the regulation and general advice regarding animal husbandry (SJVFS 2010:15) it is stated that animals should be kept in thermal comfort. Animals have thermal comfort within the thermoneutral zone, where the animals can maintain their heat balance without any difficulty. The thermoneutral zone is restricted by the lower and upper critical temperature. When the temperature in the environment is lower than the lower critical temperature, the animal needs to increase their metabolism to maintain their body temperature. When the temperature in the environment instead is higher than the upper critical temperature the animals will start to sweat or pant, in an attempt to lower the body temperature. If they cannot get rid of the excess heat the body temperature will increase. No measurement of the thermal comfort is made in Sweden today, during the official dairy farm inspections. The aim of this study was therefore to examine if it is possible to measure cows’ thermal comfort by measuring their heat loss. Temperature measurements were collected from 20 dairy cows (eleven Swedish Red and White cattle and nine Swedish Holstein), at Lövsta the Swedish Lifestock Research Centre at SLU, Uppsala. The temperature measurement methods examined, were one rectal thermometer (Microlife AG, model MT20RA), one skin temperature meter (DM852), one IR meter (TN1) and two IR cameras (FLIR E8 and FLIR C2). The skin temperature meter and the IR meter were used to measure the temperature both ten centimeters below the hip bump and at the neck, while the IR meter also were used to measure the temperature at the vulva. The rectal thermometer was used to measure the temperature seven to eight centimeters into the rectum and photos were taken with both IR cameras at the eye, udder and vulva. The measurements were conducted monthly during the study period (6th February, 8th February, 10th February, 9th March, 19th April, 17th May, 21th June, 18th July, 30th August, 27th September, 13th October, 7th November, 13th December and 18th January). A weather station (Nexus prologue, model: IW004/36-5136) was used to measure the temperature and relative humidity in the middle of the stable. The mean temperatures and variance calculated for the lactating- and dry cows were used to make charts that evaluated and compared the measurement methods. The cows’ milk yield was also obtained and compared to the mean udder temperature. The conclusion was that the IR meter was most suitable to measure the cows’ thermal comfort, because the mean temperature followed the housing temperature the most and the variance was low even if the housing temperature increased. The skin temperature meter and the IR camera FLIR C2 was after the IR meter the measuring methods that were most suitable to measure the cows’ thermal comfort. These measuring methods was less suitable compared to the IR meter because they followed the housing temperature less and generated a larger variance. The measuring methods that was the least suitable to measure the cows’ thermal comfort were the rectal thermometer and the IR camera FLIR E8. It is however important to remember that the result for the IR cameras could have been different if different measuring locations would have been chosen. More research is needed to construct the most effective method to measure cows’ thermal comfort. It is also important to look at the farmers’ perspective and generate a method that they practically can use to improve the cows’ thermal comfort.